Response of rice (Oryza sativa) varieties of different durations to level of nitrogen in coastal alluvial soils of Orissa in wet season - Rao, K S; Moorthy, B T S (The Indian Journal of Agricultural Sciences, 2012)
A field experiment was conducted during the wet season of 1991-93 in Coastal alluvial soils of Cuttack (high-rainfall region), to identify suitable varieties of rice (Oryza sativa L.) of different maturity durations and their response to nitrogen application. The promising varieties with higher yield potential identified were 'Gayatri', 'Pankaj' and 'IET 8002' in the long-duration group (150-165 days); 'IR 36'., 'IET 9979' and 'IET 8585' in the medium-duration group (125-135 days); and 'IET 8887' and 'IET 8944' in the short-duration group (95-105 days). The mean optimum and yield-maximizing N doses were respectively 84.7 and 89.5 kg/ha for long-duration group, 75.6 and 83.4 kg/ha for medium group and 38.1 and42.1 kg/ha for early group. Long-duration photo-sensitive varieties of 150-165 days were the highest yielders (mean yield 4.2 tonnes/ha in 2 years), responding better to N application than other groups of varieties.